Measuring perceived competence and global self-worth in children: implications for Australian boys and girls in the physical domain / Elizabeth Rose and Dawne Larkin - Rose, Elizabeth; Larkin, Dawne (Faculty of Sports Science and Recreation, 2005)
In this study we examined the validity of the Self-Perception Profile Children (SPPC; Harter, 1985) with 8 to 11 year old Australian girls (n = 200) and boys in = 180). We also looked at the relationship between perceived athletic competence and actual movement competence as measured by the MAND (McCarron, 1982). Although some correlations between athletic self-perceptions and actual motor competence were significant, they were low and varied by age and gender. ANOVAs revealed differences across gender and grade. Interactions for physical appearance and global self-worth showed girls' self-perceptions lowered from grade 4 to 6. First and second-order factor analyses for the total sample and the girls subsample supported Harter's model, but the factor pattern for boys differed. The differences found between girls and boys demonstrate the importance of examining their developmental responses separately.